Characteristics of Cataract Surgery at the Banten Regional General Hospital in 2024 - Java Indra Maulana S; Syifa Husna Mahmudah (CV. Publikasi Indonesia, 2026)
Cataract is the leading cause of treatable blindness worldwide. Cataract surgery has undergone significant evolution in recent decades, with phacoemulsification becoming the technique of choice in developing countries. This study aims to analyze the characteristics of cataract surgery techniques performed at Banten Regional General Hospital in 2024. This study used a descriptive research design with a cross-sectional approach. Data were obtained from medical records of patients who underwent cataract surgery at Banten Regional General Hospital from January to December 2024. Inclusion criteria included all patients who underwent cataract surgery at Banten Regional General Hospital in 2024. Exclusion criteria included incomplete medical records. Based on the research, a total of 631 cataract surgery cases were found in 2024. The distribution of surgical techniques showed phacoemulsification with intraocular lens (IOL) implantation as the dominant technique, with 625 cases (99.0%), followed by extracapsular cataract extraction (ECCE) with 3 cases (0.5%), and other procedures each with 1 case (0.2%). Monthly distribution showed the highest peak in August (96 cases, 15.2%) and the lowest in December (19 cases, 3.0%). In conclusion, phacoemulsification with IOL is the most dominant cataract surgery technique at Banten Regional General Hospital in 2024, demonstrating the adoption of modern technology in ophthalmology services at regional hospitals.